Predicting factors impacting EFL students’ writing competence: Examining the moderating effects of personal characteristics - Phe Quang Chu; Trang Hoang Trang; Dao Thi Anh Vo (Ho Chi Minh City Open University Journal of Science - Social Sciences)
This paper quantitatively predicts the factors that impact English as a Foreign Language (EFL) students’ Writing Competence (WC), examining the multiple-level effects of three independent constructs (Environmental Factors [EF], Personal Beliefs [BL], Behavioral Factors [BF]) and three moderating variables (gender, academic performance, and self-study time) on EFL students’ WC. The questionnaire was delivered to 85 EFL students at a university in Vietnam, and the findings show that the SRMR index of the estimated model is .46, meaning a good fit. Hypothesis testing validated the positive causality between the exogenous constructs and their corresponding endogenous ones. In the direct relations, EF affects BL the most (75.1%), BF impacts WC (69.3%), and finally, BL influences BF the least (38.4%). In the indirect relations, EF affects WC the most (55.1%), then EF influences BF (28.9%) and finally, BL impacts WC the least (26.6%). The analytical result also revealed the moderating effect of gender on the relation between BF and WC. Still, the moderation of academic performance and self-study time on the relation between BF and WC was rejected. Finally, the authors discuss some major administrative measures to target if stakeholders wish to improve EFL students’ WC.